2016
DOI: 10.1177/2043610616676036
|View full text |Cite
|
Sign up to set email alerts
|

Digital play: Exploring young children’s perspectives on applications designed for preschoolers

Abstract: This study builds on and contributes to research on digital play with young children. Previous research has examined digital play from different viewpoints, but no studies have specifically addressed young children's perspectives as they interact with applications (apps) that have been designed specifically for their age group. While our review of the literature provides insights from investigations of young children's perspectives, there is limited research on preschoolers' views on the apps designed for them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 20 publications
(27 reference statements)
0
28
0
5
Order By: Relevance
“…Several studies offer close observations of a small number of pre-school children using digital media in the home, sometimes undertaken by the children's parents or grandparents acting as researchers. These studies (Geist, 2012;Harrison and McTavish, 2016;O'Mara and Laidlaw, 2011;Verenikina and Kervin, 2011) offer insights into children's use of tablets in home contexts. The researchers note the fluidity with which children engage with the technical aspects of using tablets, in addition to the playful nature in which children use them as they watch videos or look at photographs.…”
Section: The Digital Practices Of Under Threesmentioning
confidence: 99%
“…Several studies offer close observations of a small number of pre-school children using digital media in the home, sometimes undertaken by the children's parents or grandparents acting as researchers. These studies (Geist, 2012;Harrison and McTavish, 2016;O'Mara and Laidlaw, 2011;Verenikina and Kervin, 2011) offer insights into children's use of tablets in home contexts. The researchers note the fluidity with which children engage with the technical aspects of using tablets, in addition to the playful nature in which children use them as they watch videos or look at photographs.…”
Section: The Digital Practices Of Under Threesmentioning
confidence: 99%
“…More recent research in the area of family literacy with a special focus on digital media and digital devices also informs this study. Verenikina and Kervin (2011) embarked on a case study of a small sample of three families with one or more children of preschool age, focusing on the preschool children's engagement with tablet applications (apps) that are geared towards children. Their study was in three parts -open-ended, semi-structured interviews with parents regarding their children's use of digital devices and apps; a review and selection of two educational apps geared to preschool-age children; and video-recorded observations of preschool children engaging in the apps from part two on a tablet.…”
Section: Family Literacymentioning
confidence: 99%
“…A similar study conducted by Holloway et al (2013) found an emerging trend in many European countries of toddlers and preschoolers using Internet connected devices such as tablets and smartphones for entertainment and communication (p. 4). As new digital devices continue to become an integral part of everyday life, young children increasingly incorporate them in their daily literacy practices by using them as play objects at home (Burke & Marsh, 2013;Verenikina & Kervin, 2011).…”
Section: Digital Devices and Early Literacymentioning
confidence: 99%